Phylogeny of Amphidinium (Dinophyceae) from Guam and Okinawa, with descriptions of A. pagoense sp. nov. and A. uduigamense sp. nov. Issue 3 (4th May 2022) - Phua, Yong Heng; Husnik, Filip; Lemer, Sarah; Wakeman, Kevin C.
ABSTRACT: Marine benthic dinoflagellates within the genus Amphidinium were isolated from Guam and Okinawa. Isolated strains were identified to species-level using phylogenetic analyses of 28S rRNA and ITS-5.8S rRNA genes as well as microscopy. Of the six isolated strains, two were new species: A. pagoense sp. nov . and A. uduigamense sp. nov . Other isolates included strains of A. massartii and A. operculatum from Guam, and two strains of A. operculatum from Okinawa. Both new species were described using light and electron microscopy (SEM and TEM). The combination of characteristics that make A. pagoense sp. nov . unique includes a pair of centrally-located pyrenoids, variable cell shape, absence of scales and a long, curved ventral ridge. For A. uduigamense sp. nov ., a combination of several morphological features distinguishes it from other species. These include a constriction near the anterior of the hypocone, two centrally located pyrenoids, a longitudinal flagellum inserted in the posterior one-third of the cell, cell size, cell division in the motile stage and the absence of scales. Toxicity was confirmed in these two novel species by testing methanol extracts in an Artemia bioassay. Previously unrecorded ITS rRNA gene sequences from A. operculatum were also sequenced from both locations. Species identified and newly described in this study expand the taxonomic knowledge of Amphidinium in the Pacific.